FAKTOR-FAKTOR YANG MEMPENGARUHI PERINGKAT OBLIGASI PADA PERUSAHAAN KEUANGAN (PERIODE 2012-2015) - Rendy Anggara, 13.05.52.0134; Lisiantara, G. Anggana (Students Journal of Accounting and Banking, 2017)
The study examines the effect Profitability, Liquidity, Leverage, Company Size, Secure, Mature, and Auditor Reputation on Bond Rating. The population in this research is financing companies that issued the bond and listed in Indonesian Stock Exchange period 2012-2015. The sampling method used purposive sampling with the observation period from 2012 to 2015. Relationship and (or) influence between variable is described by using multiple regression analysis. The result of this study indicate that Liquidity and Company Size has negative effect on Bond Rating. Whereas Leverage, Mature, and Auditor Reputation has positive effect on Bond Rating, also Profitability and Secure has no effect on Bond Rating.Keywords: Bond Rating, Profitability, Liquidity, Leverage, Company Size, Secure, Mature, and Auditor Reputation